Impact of Bilateral Infiltrates on Inflammatory Biomarker Levels and Clinical Outcomes of Children With Oxygenation Defect. Issue 6 (June 2020) - Kohne, Joseph G.; Dahmer, Mary K.; Weeks, Heidi M.; Kaciroti, Niko; Quasney, Michael W.; Sapru, Anil; Curley, Martha A. Q.; Matthay, Michael; Flori, Heidi
Abstract : Objectives: The 2015 definition for pediatric acute respiratory distress syndrome did not require the presence of bilateral infiltrates. We tested the hypothesis that pediatric patients meeting oxygenation criteria for pediatric acute respiratory distress syndrome but without bilateral infiltrates would have different inflammatory biomarker levels and clinical outcomes than those with bilateral infiltrates. Design: Secondary analysis of a prospective cohort study. Setting: Twenty-two PICUs. Patients: Four-hundred forty-six patients age 2 weeks to 17 years intubated for respiratory failure with oxygenation index greater than or equal to 4 or oxygenation saturation index greater than or equal to 5 on the day of intubation or the day after. Interventions: None. Measurements and Main Results: Patients with bilateral infiltrates, either on the day of intubation or within the following 2 days, were compared with children who never developed bilateral infiltrates. Two analyses were performed to test 1) whether bilateral infiltrates are associated with elevated interleukin-1 receptor antagonist or interleukin-8 and 2) whether bilateral infiltrates are associated with worse clinical outcomes. Patients with bilateral infiltrates more often had a primary diagnosis of pneumonia (41% vs 28%; p = 0.02) and less often asthma (8% vs 23%; p < 0.01). After controlling for age, gender, and primary diagnosis, interleukin-1 receptor antagonist was higher on study days 1 and 2 in patients with bilateral infiltrates. There was no difference in interleukin-8 levels. After adjusting for age, gender, Pediatric Risk of Mortality score, and severity of oxygenation defect, presence of bilateral infiltrates was associated with longer duration of mechanical ventilation in survivors (hazard ratio, 0.64; 95% CI, 0.49–0.82; p < 0.01); this association was independent of primary diagnosis. Overall mortality was 9%; mortality was higher in those without bilateral infiltrates (14% vs 8%; p = 0.04). Conclusions: Children meeting pediatric acute respiratory distress syndrome oxygenation criteria with bilateral infiltrates on chest radiograph experience a more intense early inflammatory response. Bilateral infiltrates are associated with longer time on the ventilator independent of oxygenation defect severity. Abstract : Supplemental Digital Content is available in the text.